RESEARCH AND INITIAL EDUCATION IN PHYSICAL EDUCATION: CERTAIN CONSIDERATION (Fiep Bulletin - online, 2015)
University is a properly place for professional formation and appearance of researches. Therefore the objective of this research is to accomplish a bibliographical discussion on important subjects about research in undergraduation of Physical Education. Subjects that will be approached during this study will observe in literature how research is worked in the university as a teaching method for the formation of future professionals. Researches on this thematic comment that in the academic environment there is a consensus speech relating the theoretical subjects with practical. Likewise in this perspective of formatting a reflexive professional, researches point the necessity of research in the initial formation. However, the investigation activity in the undergraduation should not be cultivated with few students. Besides all that, it is important to consider that research is not the end, but actually a part of the way. Due to see the researching action as the end, it  conceives the investigation as only a simple discovery action and not as a matter to analyze and reflect. So, when research is used as tool of practice in the undergraduation, the same one should be linked to a reflection moment, transforming the teaching practice a way to conquer knowledge and  development to apply reasonable tasks for the population.
Keywords: Researches; Undergraduation; Professional Performance.